2020
DOI: 10.2217/fca-2020-0082
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in COVID-19 patients, a Report of Three Cases

Abstract: The mortality rate of coronavirus disease-19 (COVID-19) has been reported as 1–6% in most studies. The cause of most deaths has been acute pneumonia. Nevertheless, it has been noted that cardiovascular failure can also lead to death. Three COVID-19 patients were diagnosed based on reverse transcriptase-polymerase chain reaction of a nasopharyngeal swab test and radiological examinations in our hospital. The patients received medications at the discretion of the treating physician. In this case series,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 15 publications
0
45
0
1
Order By: Relevance
“…One of the challenging issues in COVID-19 treatment is unwanted QT prolongation and risk of drug induced malignant arrhythmias, especially in the ICU patients with multiple comorbidities. [8,9]. Combining hydroxychloroquine with additional antiviral drugs such as lopinavir/ritonavir (which are both potent CYP3A4 inhibiting drugs) and azithromycin might result in higher plasma levels and a significant QT prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenging issues in COVID-19 treatment is unwanted QT prolongation and risk of drug induced malignant arrhythmias, especially in the ICU patients with multiple comorbidities. [8,9]. Combining hydroxychloroquine with additional antiviral drugs such as lopinavir/ritonavir (which are both potent CYP3A4 inhibiting drugs) and azithromycin might result in higher plasma levels and a significant QT prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of cardiac atrial and ventricular rhythm disorders have been reported in COVID-19 patients including atrial fibrillation, sinus tachycardia and bradycardia, complete conduction block and cardiac arrest [ 82 ]. Arrhythmia may associate with sudden cardiac death, which is a pathologic outcome also observed in COVID-19 patients [ [83] , [84] , [85] ]. Arrhythmia in COVID-19 patients is associated with myocardial injury and is thought to reflect the severity of illness [ 81 , 86 , 87 ].…”
Section: Sex Differences In Covid-19-related Cardiovascular Injurymentioning
confidence: 99%
“…Infections by certain viruses like influenza and parvovirus B-19 are known to be some of the most common causes of myocarditis [ 46 , 47 ]. Autopsy reports of COVID patients show the presence of myocyte necrosis with lymphocytes in vicinity, suggestive of viral myocarditis [ 48 ].…”
Section: Cardiovascular Involvement In Covid-19 Patientsmentioning
confidence: 99%
“…A massive release of cytokines consequent to T-cell activation (IL-1, IL-10, IL-12, IL-6, IL-7, IFN-γ, TNF-α, CXCL10, CSF, etc.) may lead to direct myocardial fiber injury [ 9 11 , 29 , 41 , 46 , 51 , 52 ]. Cytokines such as TNF and IL-15 can directly induce myocardial fiber dysfunction, leading to stunning of the myocardium and poor contractile function [ 53 ].…”
Section: Cardiovascular Involvement In Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation